Smooth motion target displacements during eye blinks - Neo, Chloe Li Yan (2019)
This study investigates the relationship between the motion of a visual target and the perceived position of the target after eye blinks. Eye blinks disturb the visual feedback, and this will reduce the information received to process in the brain. This lapse of visual input is not noticed during spontaneous blinks. However, when blinks occur during the perceiving of a motion, it is unclear if participants would realise the errors when the continuity of the target’s motion is compromised. This study investigates the prediction of motion during the blink by analysing the perception of the participants when there is a target displacement in a target with a smooth motion trajectory. It considered whether the direction across a horizontal plane and velocity would affect the prediction of motion. Looking at the literature, it is hypothesised firstly that there would be an undershoot of the perception of motion when blinks occur. Secondly, this perception would be unaffected by horizontal directional difference. Lastly, there would be a difference in the perception of motion at different velocities during the blinks. A behavioural responses task was conducted using a smooth motion target stimulus. This study found that while there is no significant difference in the perception of the smooth motion stimulus when it travels in different directions, there is a significant difference in the perception of the smooth motion stimulus at different velocities. This has implications for the perception of time during blinks and opens up avenues to explore how the brain compensates for errors caused by blinks.